Prolonged exposure therapy and its implication through telehealth - Esmail, Mustafa E.; Zarei, Traad L.; Rayyani, Sarah A.; Aljoaid, Rami A.; Derar, Jumana M.; Alharban, Yousef S.; Gassem, Jumana S.; Mominkhan, Fatimah A.; Albolushi, Sara A.; Alkhalifa, Rayan O.; Alharbi, Eid M. (International Journal Of Community Medicine And Public Health, 2021)
Patients with post-traumatic stress disorder (PTSD) usually suffer from avoidance symptoms which might intervene against seeking adequate healthcare and medical consultation for their conditions. As a result of the reduced support to these patients, it has been demonstrated that PTSD symptoms usually persist based on the continuous feeling of avoidance among them. Evidence indicates the efficacy of prolonged exposure therapy for PTSD patients that are usually exposed to traumas as anger issues, comorbid depression, guilt, and alcohol overuse conditions. In the present literature review, we have discussed the concept of conducting prolonged exposure therapy for patients with PTSD and the different implications and effectiveness of telehealth in this field. Evidence indicates the effectiveness of prolonged exposure therapy in managing PTSD regarding symptoms reduction of intensity and improvement. Conducting the therapy through telehealth was also reported with favorable outcomes comparable with the outcomes of the in-person interviews with no adverse events. However, drop-outs have been reported to be high among telehealth-mediated sessions, and therefore, serious approaches should be exerted to overcome these issues. Further considerations should also be provided for patients in certain situations as pandemics to enhance the quality of treatment. Finally, further research is still needed to target areas with poor access to telehealth-related modalities, and introduce the modality to the affected populations and urge local health authorities to provide easy accessibility to these patients.